Rheological properties of flaxseed meal and soybean protein isolate blend by extrusion - Siqin, Li; Min, Wu; Donglin, Zhao; Yi, Liu; Yang, Sun; Dong, Li (International Journal of Agricultural and Biological Engineering, 2017)
The rheological properties of flaxseed meal (FM) and Soybean Protein Isolate (SPI) extruded by the two-screw extruder under different processing conditions were investigated. Moisture, temperature, screw speed and SPI concentration were the four major factors for the extrusion process. The rheological properties of extruded products were calculated by steady state flow test, frequency sweep test and creep test. All the samples showed shear-thinning effect that is to say their apparent viscosities decreased with the increases of shear rate. The data fitted well to Power Law model. It was found that both the storage (G′) and loss modulus increased as the rise in the angular frequency (w), which also fitted well to Power Law model. The creep-recovery behavior of the samples fitted well to Burger’s model. In addition, the temperature had no significant effect on the creep recovery rate of the samples.Keywords: flaxseed meal (FM), soybean protein isolate (SPI), extrusion, rheological propertiesDOI: 10.25165/j.ijabe.20171004.2734Citation: Li S Q, Wu M, Liu Y, Sun Y, Li D. Rheological properties of flaxseed meal and soybean protein isolate blend by extrusion . Int J Agric & Biol Eng, 2017; 10(4): 224–233.